The value of social, behavioral, and economic sciences to national priorities : a report for the National Science Foundation (Consensus study report., 2017)
"Nearly every major challenge the United States faces--from alleviating unemployment to protecting itself from terrorism--requires understanding the causes and consequences of people's behavior. Even societal challenges that at first glance appear to be issues only of medicine or engineering or computer science have social and behavioral components. Having a fundamental understanding of how people and societies behave, why they respond the way they do, what they find important, what they believe or value, and what and how they think about others is critical for the country's well-being in today's shrinking global world. The diverse disciplines of the social, behavioral, and economic (SBE) sciences --anthropology, archaeology, demography, economics, geography, linguistics, neuroscience, political science, psychology, sociology, and statistics--all produce fundamental knowledge, methods, and tools that provide a greater understanding of people and how they live. The Value of Social, Behavioral, and Economic Sciences to National Priorities evaluates whether the federal government should fund SBE research at the National Science Foundation (NSF), and, specifically, whether SBE research furthers the mission of the NSF to advance national priorities in the areas of health, prosperity and welfare, national defense, and progress in science; advances the missions of other federal agencies; and advances business and industry, and to provide examples of such research. This report identifies priorities for NSF investment in the SBE sciences and important considerations for the NSF for strategic planning"--Publisher's website.